Painel de expressão gênica como biomarcador no hipotiroidismo por transcriptoma RNA-seq em indivíduos com hipotiroidismo primário - Almeida, Robson José de (2016)
The thyroid hormone (TH), modulates directly and indirectly the primary physiological processes for the development and maintenance of the human body. The neuroendocrine activity provides an integration of complex functions of tissues, generating coordinates answers the specific needs of the body. The hypothalamus, pituitary, thyroid is the classic example of the neuroendocrine control. Hypothyroidism is defined by the thyroid gland unable to produce HT sufficient to meet the metabolic needs of the body. The plasma determination of thyroid stimulating hormone (TSH) is the first test performed on suspicion of primary hypothyroidism. The accuracy of diagnosis of TSH for Hypothyroidism detection still has limitations. Currently the specific molecular diagnostics for thyroid diseases are mostly made for thyroid carcinomas. RNA-Seq (ribonucleic acid sequencing) is currently built by technology called NGS (next generation sequencers) and performs all of the transcripts profile massively. TSH levels and free T4 set to most individuals in euthyroid may not reflect the proper amounts of hormone for the proper functioning of all tissues. The objective of this study was to identify the pattern of gene expression in peripheral blood of patients with hypothyroidism and find a gene or a panel of genes able to differentiate eutiroidianos individuals from patients with primary hypothyroidism. We have identified 5 genes (CCNJL, IMPA2, FAM129B, SLC4A11 and CDK18) that may be useful to form a panel of biomarkers for the ability to differentiate euthyroid primary hypothyroidism and also correlate them with the serum levels of TSH.